FROM EXCLUSION TO BELONGING: ASSESSING WOMEN'S PERCEPTION OF PUBLIC OPEN SPACES - Malhotra, Arushi; Aulakh, Rawal Singh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Public open spaces are integral to urban landscapes, offering chances for interaction, recreation, and community engagement. However, their design and management profoundly influence diverse user experiences and perceptions. Women's experiences of public open spaces are often shaped by a complex interplay of factors, including social norms, safety concerns, and the physical environment. This research aims at deciphering the complex relationship between women, gender, and their perceived place within these spaces. Drawing on qualitative research methodologies including Ethnography, on site semi-structure interviews and site observations, the study scrutinizes women's perceptions and interactions in these spaces, highlighting the ways these interactions shape their sense of place. This study further explores the confluence of gender and placemaking, providing a nuanced understanding of the social, cultural, and physical factors influencing women's experiences in such spaces. By offering strategic insights and recommendations, the research envisages facilitating the creation and governance of public open spaces that respect gender equality and social inclusion.